Sequestrectomy or microdiscectomy in patients with lumbar disc herniation (Annals of Medical Research, 2021)
None
Keywords: Lumbar Disc Herniation; Microdiscectomy; Postoperative Analgesic Use; Sequestrectomy; Visual Analogue Scale.